Alone in Berlin [videorecording (DVD)] - Perez, Vincent, 1964-; Thompson, Emma; Gleeson, Brendan; Brühl, Daniel, 1978-; Fallada, Hans, 1893-1947 (IFC Films, 2017)
How did an ordinary, middle-aged couple become a symbol of defiance against Nazi brutality? This tale of courage unfolds against the tumultuous backdrop of Berlin in 1940. Otto and Anna Quangel are a working class husband and wife doing their best to ride out the war. Their son is killed fighting on the frontlines. They begin pouring their rage and grief into postcards emblazoned with anti-Nazi slogans, risking everything to disseminate their messages of protest across the city.